2012
DOI: 10.1002/dmrr.2256
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy as treatment of diabetic foot ulcers

Abstract: SummaryHyperbaric oxygen therapy (HBO) could be described as a short-term, highdose oxygen inhalation and diffusion therapy, delivered systemically through airways and blood, achieved by having the patient breathing concentrated oxygen at a pressure higher than 1 absolute atmosphere. In clinical practice, monoplace or multiplace hyperbaric chambers are used to achieve this. Treatment is usually given as daily 90-to 120-min-long HBO sessions at pressures between 2.0 and 2.5 absolute atmosphere, aiming for 30-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 57 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…There is increasingly strong evidence that hyperbaric oxygen therapy can significantly improve the healing of diabetic wounds in the short term (12, 13) and the authors used this modality as an adjunctive therapy to improve wound healing in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasingly strong evidence that hyperbaric oxygen therapy can significantly improve the healing of diabetic wounds in the short term (12, 13) and the authors used this modality as an adjunctive therapy to improve wound healing in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…HBO can be applied as an adjunctive therapy for patients with severe soft tissue foot infections and osteomyelitis who have not responded to conventional treatment, though the available data are insufficient [32, 71, 72, 109, 110]. …”
Section: Discussionmentioning
confidence: 99%
“…A review of 6 studies prepared by Roeckl-Wiedmann et al [69] demonstrated that additional application of HBOT reduced the risk of amputation in 118 patients. Other double-blinded, randomized, and placebo-controlled clinical trials presented by Löndahl et al [33, 70, 71] proved applicability of HBOT in DFU adjunct therapy. Complete healing of the index ulcer (acc.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 98%
“…Hyperbaric oxygenation (HBO 2 ) is the therapeutic or experimental application of 100% oxygen at a pressure level higher than atmospheric pressure [1,2]. The delivery of oxygen under high pressure increases arterial and tissue pO 2 in the body and this has beneficiary effects on many conditions where reduced tissue oxygenation does not meet the metabolic needs.…”
Section: Hyperbaric Oxygen Use In Disorders With Vascular Damagementioning
confidence: 99%
“…With HBO 2 , the amount of dissolved oxygen in the plasma increases, facilitating delivery of oxygen independent of hemoglobin [3,4]. This is achieved by various patterns of hyperbaric exposure, mostly with repetitive hyperbaric sessions ranging from 90-120 min at pressures of 2.0-2.5 bar, used on humans with clinical conditions or on animals as experimental models [1,2,5,6,7]. HBO 2 is clearly connected with beneficial effects for some conditions with vascular pathology.…”
Section: Hyperbaric Oxygen Use In Disorders With Vascular Damagementioning
confidence: 99%